Influence of Community Policing Strategies by Non-State Actors on Youth Radicalization in Kamukunji Sub-County: A Case of Kamukunji Community Peace Network (International Journal of Scientific Research and Management (IJSRM), 2025)
This study examined the role of non-state actors in countering youth radicalization, focusing on community policing strategies adopted by the Kamukunji Community Peace Network (KACPEN) in Nairobi County, Kenya. The objective was to identify the forms of community policing strategies associated with counter-radicalization in Kamukunji Sub-County. The study was guided by Schemas Theory, which explains how cognitive frameworks shape community responses to radicalization. A convergent parallel mixed methods design was used, targeting 4,242 registered KACPEN members, including religious leaders, youth groups, and peace builders. A sample of 98 respondents was selected. Data were collected using questionnaires and in-depth interviews, analyzed through descriptive statistics (SPSS v24) and thematic analysis. Findings revealed that community involvement, police foot patrols, and partnerships were central strategies, while public participation occurred mainly through community-based programs and youth engagement. However, most respondents were unaware of media laws related to radicalization. The study concludes that non-state actors significantly enhance resilience to extremism and recommends stronger state, community collaboration, awareness of legal frameworks, and sustained support for community policing initiatives.